Using the ISO 56002 Innovation Management System: A Practical Guide for Implementation and Building a Culture of Innovation - Benraouane, Sid Ahmed; Harrington, H. James (Routledge, 2021)
In 2019, ISO Technical Committee 279 released a new international standard on innovation management system called ISO 56002:2019. The objective of this standard is to provide a framework on how to build an innovation ecosystem that can be sustained over time. Similar to the quality management system that ISO established decades ago, this standard provides instructions related to best practices on how to manage innovation activities, projects, and programs. It does not describe detailed activities within the organization, but rather provides guidance at a general level. It does not prescribe any requirements or specific tools or methods for innovation activities. Essentially, the standard does not provide guidance on how to implement and/or use the standard. The standard basically tells you what to do and document -- this powerful book tells you how to do it. The techniques in this book are directed at key tasks across the innovative process, such as maximizing quality, productivity, maintainability, usability, and reliability, while focusing on reducing the product cycle time and costs within the innovative process. Currently, there are no other comprehensive books available on how to fully implement this standard in companies -- This book is crucial for managers, business leaders, entrepreneurs, and consultants looking for help to reap the benefits of an innovation management system. This book takes you step by step through the process of developing an innovation ecosystem. In addition, it provides frameworks, tools, methodologies, cases, and best practices so your organization can experience the full value of the standard. The objective of this standard is to provide a framework on how to build an innovation ecosystem that can be sustained over time. Similar to the quality management system that ISO established decades ago, this standard provides instructions related to best practices on how to manage innovation activities, projects, and programs.